A Review of Zakat Studies in ASEAN - Irma Durrotun Niswah (Ekonomi Islam Indonesia, 2020)
This study aims to determine the map of the development of zakat research in ASEAN. The data analyzed were 115 publications on zakat research publications. Map of the development of waqf research is obtained through the export process into the .txt file format. The export data is then processed and analyzed using the VOSviewer application program to find out the bibliometric map of the development of zakat research in ASEAN. The results showed that the number of publications on the development of zakat research from 2007-2019 increased significantly and was the most published in the International Journal of Business and Social Science and The Journal of Muamalat and Islamic Finance Research (JMIFR), as well as the most cited publications namely Motivations of Paying Zakat on Income: Evidence from Malaysia. The authors who published the most research results on zakat in ASEAN were Ahmad Fahme Mohd Ali and Muhammad Ridhwan Abdul Aziz. Research related to zakat is mostly done in Malaysia, where the approach used is qualitative. Network visualization shows that the co-word map of the development of zakat research is divided into 19 clusters, the visualization of density co-author of research related to zakat management in ASEAN, both related and unrelated divided into 2 clusters. There is also a visualization of the co-sources network map divided into 13 clusters, where each cluster consists of 1 journal. Keywords: Zakat; Bibliography; ASEAN